In Situ X-ray Absorption Spectroscopy Studies of Discharge Reactions in a Thick Cathode of a Lithium Sulfur Battery. Issue 2 (1st January 2017) - Wujcik, Kevin H.; Wang, Dunyang Rita; Pascal, Tod A.; Prendergast, David; Balsara, Nitash P.
Abstract : Lithium sulfur (Li-S) batteries are well known for their high theoretical specific capacities, but are plagued with scientific obstacles that make practical implementation of the technology impossible. The success of Li-S batteries will likely necessitate the use of thick sulfur cathodes that enable high specific energy densities. However, little is known about the fundamental reaction mechanisms and chemical processes that take place in thick cathodes, as most research has focused on studying thinner cathodes that enable high performance. In this work, in situ X-ray absorption spectroscopy at the sulfur K-edge is used to examine the back of a 115 μm thick Li-S cathode during discharge. Our results show that in such systems, where electrochemical reactions between sulfur and lithium are likely to proceed preferentially toward the front of the cathode, lithium polysulfide dianions formed in this region diffuse to the back of the cathode during discharge. We show that high conversion of elemental sulfur is achieved by chemical reactions between elemental sulfur and polysulfide dianions of intermediate chain length (Li2 Sx, 4 ≤ x ≤ 6). Our work suggests that controlling the formation and diffusion of intermediate chain length polysulfide dianions is crucial for insuring full utilization of thick sulfur cathodes.